Preventative approaches to falls and frailty - Seiji Hashimoto; Tatsuya Hosoi; Mitsutaka Yakabe; Makoto Yunoki; Shoya Matsumoto; Yoshitaka Kase; Masashi Miyawaki; Masaki Ishii; Sumito Ogawa (Osteoporosis and Sarcopenia, 2025)
With increasing life expectancy, the aging population grows, leading to more age-related diseases. Among these, falls are a serious public health issue, as they cause disability in older adults and impose a significant burden both on caregivers and society. Despite numerous studies on fall risk and prevention, the incidence of falls among older adults has not shown any significant improvement. Given the multifactorial nature of falls, it is necessary to evaluate risk factors comprehensively. Recently, the Comprehensive Geriatric Assessment, a tool for comprehensively evaluating older adults, has been reported to help prevent falls and improve postfall outcomes. Assessing individual risks and effectively integrating exercise, nutrition, and appropriate medication management into multifactorial interventions is essential for developing effective fall prevention strategies.